Magnetic configuration scans during divertor operation of Wendelstein 7-X. (4th January 2022) - Andreeva, T.; Geiger, J.; Dinklage, A.; Wurden, G.; Thomsen, H.; Rahbarnia, K.; Schmitt, J.C.; Hirsch, M.; Fuchert, G.; Nührenberg, C.; Alonso, A.; Beidler, C.D.; et al.
Abstract: Wendelstein 7-X (W7-X) (Greifswald, Germany) is an advanced stellarator, which uses the modular coil concept to realize a magnetic configuration optimized for fusion-relevant plasma properties. The magnet system of the machine allows a variation of the rotational transform (iota) at the boundary. In the latest W7-X operational phase a dedicated configuration scan has been performed varying the rotational transform between magnetic configurations with iota = 5/4 and iota = 5/5 at the boundary. This paper presents an overview of the experiments and of the main results with respect to confinement and stability. The main observation is an increase of the plasma energy in several intermediate configurations of the scan when the 5/5-islands are close to the plasma boundary but still inside the last-closed-flux-surface. In addition, these configurations showed marked MHD-activity with a crashing behavior related to the 5/5-islands. The corresponding mode amplitude was correlated with the size of the internal 5/5 islands.